ETHNOPOLITICAL ORGANIZATION IN THE METROPOLITAN REGION OF BUENOS AIRES, ARGENTINA - Engelman Garreta, Juan Manuel (2019)
The present paper describes how indigenous leaders revert their subordinate position trough their local and ethno-political practice, according to different negotiation instances. The following reflections arise from the ethnographic work with a group of diverse indigenous communities established in the municipality of Almirante Brown of the Metropolitan Region of Buenos Aires, who since the beginning of the 2000 year have beenprotagonizing a visibility and local ethno-political organization process.